The Communication between a Child Patient who was Exposed to Domestic Violence and the Medical Team - Seyyare Duman (Dilbilim Araştırmaları Dergisi)
The aim of this study is to reveal the dimensions of the interaction between the child patient and the health team responsible for delivery. The communication model between the patient and the medical team, namely the nurse and the other personnel, is similar to the communication model between the doctor and the patient. in this model communication is health-, not patient-oriented. In this study, however, communication is not health-oriented. The subject has become pregnant as a result of incest. The medical team who are aware of this fact treat her in a privileged manner. This special treatment not shown to other patients is strategic and is for the benefit of the patient. In this way the patient not only receives special treatment but she can also find the opportunity to express herself better than other patients. By this strategy, the medical team fulfill their responsibility. However, there are disadvantages for the patient in this communication model as well. The medical team puts impositions on the patient by giving orders and speak to each other about her in her presence without taking her into consideration.